2018
DOI: 10.1002/aoc.4397
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐anchored multidentate SBA‐15/di‐urea nanoreactor: A highly active catalyst for Suzuki coupling reaction

Abstract: Modification of mesoporous silica was carried out by reaction of SBA‐15 with di‐urea‐based ligand. Next, with the help of this ligand, palladium ions were anchored within the multidentate SBA‐15/di‐urea pore channels with high dispersion. The SBA‐15/di‐urea/Pd catalyst was characterized using various techniques. Theoretical calculations indicated that each palladium ion was strongly interacted with one nitrogen and two oxygen atoms from the multidentate di‐urea ligand located in SBA‐15 channels and these inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 62 publications
(92 reference statements)
2
31
0
Order By: Relevance
“…It has been reported that the size and shape of MSNs can be easily tailored by varying the temperature [7,8], reactants ratio [9], pH [10], surfactant chain length [11], as well as the addition of functional organosilanes [12]. Properly tailored MSNs found applications in numerous fields such as drug delivery systems [13,14], wastewater treatment [15,16], catalysis [17,18], fabrication of nanoreactors [19,20] and nanocontainers [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the size and shape of MSNs can be easily tailored by varying the temperature [7,8], reactants ratio [9], pH [10], surfactant chain length [11], as well as the addition of functional organosilanes [12]. Properly tailored MSNs found applications in numerous fields such as drug delivery systems [13,14], wastewater treatment [15,16], catalysis [17,18], fabrication of nanoreactors [19,20] and nanocontainers [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The N 2 sorption experiment was carried out to investigate the mesoscopic quality and textural properties of synthesized materials. As shown in Figure (a) and (b), all sorption isotherms exhibited typical IV‐type curves with clear H1‐type hysteresis loops, which was characteristic of a mesoporous structure with uniform pore size . This indicated that the ordered mesostructure was still maintained after introduction of organic moieties (viz.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the SBA-15/di-urea/ Pd nanocatalyst was achieved by the reaction of Pd(OAc) 2 with SBA-15/di-urea (Scheme 75). 54 Typical SEM image of SBA-15/di-urea/Pd reveals rod-shaped morphology aggregated into bundles (Fig. 2a).…”
Section: Scheme 34mentioning
confidence: 99%
“…52 Moreover, in 2013, Molnár published a special book chapter concerning the applications of various ordered porous materials as solid supports in Pd-catalyzed cross-coupling reactions. 45 Taking the importance of this study and following our previous publications, 8,10,23,53,54 herein, we intend to review the applications of Pd-based mesoporous silica SBA-15 as catalyst in C-C couplings. The majority of this review is about the three most important C-C coupling reactions including the Suzuki-Miyaura (S-M), Mizoroki-Heck (M-H) and Sonogashira couplings with Pd anchored on SBA-15 catalysts.…”
Section: Introductionmentioning
confidence: 95%